Efektivitas Ekstrak Kunyit (Curcuma longa L.) dan Pupuk NPK Terhadap Insidensi Penyakit Virus Keriting Kuning Pada Cabai Rawit (Capsicum frutescens L.) - Baene, Anusafati; Harahap, Rahmaniah; Harahap, Lutfi Henderlan (JURNAL AGROPLASMA, 2025)
Yellow leaf curl virus infection in chili pepper (Capsicum frutescens L.) can significantly reduce crop yield. This study aimed to evaluate the effect of turmeric extract and NPK fertilizer doses on the incidence of yellow leaf curl virus in chili pepper plants. The research was conducted at the experimental field of Universitas Pembinaan Masyarakat Indonesia from June to August 2025 using a factorial Randomized Complete Block Design (RCBD) with two factors: turmeric extract (0%, 10%, 15%, 20%) and NPK dosage (0, 3.3 g, 5 g, 6.6 g per plant), resulting in 16 treatment combinations. Disease incidence was observed from 2 to 9 weeks after transplanting. The results showed that the highest incidence occurred at weeks 3 and 8. The K3P0 treatment (high-dose turmeric without NPK) resulted in the lowest incidence rate at 11.2%, while K1P3 (low-dose turmeric + high NPK) showed the highest at 137.5%. Although ANOVA results revealed no statistically significant differences (p>0.05), descriptively, high-dose turmeric treatments reduced symptoms and spread of disease. These findings highlight turmeric's potential as an eco-friendly botanical agent for managing viral diseases in chili cultivation. Keywords: chili pepper, disease incidence, NPK, turmeric, yellow leaf curl virus